Designing Luxury Brands The Science of Pleasing Customers' Senses - Derval, Diana (Management for Professionals,, 2018)
This book shows how to build successful luxury brands using the power of sensory science and neuro-physiology. The author introduces - based on inspiring business cases like Tesla, Louis Vuitton, Chanel, Hermès, Moncler, Louboutin, or Sofitel in industries such as Fashion, Automotive or Leisure - groundbreaking scientific methods - like the Derval Color Test® taken by over 10 million people - to predict luxury shoppers' preferences and purchasing patterns and illustrates common and unique features of successful luxury brands. Through various practical examples and experiments, readers will be able to build, revamp, or expand luxury brands and look at luxury from a new angle. I myself often question the sustainability of luxury marketing, because I often fail to find the scientific explanation of many happenings of the world of luxury. This sometimes frustrates me. However, Professor Derval gives me faith in the luxury industry because she brings to the table scientific tools and approaches to creating, developing, and revamping luxury brands. I've had the pleasure to read one of her previous books "The Right Sensory Mix", and since then my understanding of the luxury market has elevated and she has brought sense to an industry driven by emotional preferences. Reading this book, I was again genuinely looking forward to acquiring more scientific tools to understand and grow the brands I service. Annie Ho, General Manager Greater China, Stella McCartney, Kering group Once again, I am very impressed with Diana Derval's new book. Through lively case studies, powerful marketing tools, and inspiring neuroscientific findings, she manages to explain the whys behind luxury mysteries. Designing luxury brands is a must read for both industry leaders and learners. Philip Kotler, , S.C. Johnson & Son Professor of International Marketing, Kellogg School of Management Luxury is first and foremost an emotion. This book will help create this emotion and unlock endless opportunities, through a deep understanding of customers. Yves Bonnefont, CEO, DS Automobiles.